ENENTUAN PARAMETER PENGELASAN RANGKA UTAMA SEPEDA MOTOR MATIC BAGIAN DEPAN MENGGUNAKAN LAS MIG OTOMATIS (PANASONIC TM-1400G3) - Yusril Irwan; Gatot Pamungkas (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
Abstract: Main frame welding at the front automatic motorcycle of PT. XXX is the stage of (trial production). The welding machine is Panasonic TM-1400G3 MIG automatic welding machine with 75% Argon and 25% Ar-CO2. Main frame material low carbon steel STAM 390G. To obtain the welding results in accordance with the standards specified by the client, weld testing parameters are varied for each test, which are ampere and voltage. The constant welding parameters in this research are travel speed, gas flow, welding direction, tip distance to workpiece, torch angle and welding angle. All test results are inspected visually and dimensionally, if passed, it will be followed by inspection of macro structure analysis. The results measured on the macro structure analysis ar : penetration (a1), penetration (a2), bead welding, throuth, leg length and crown with standard measurement values determined by the client PT.XXX. The welding results (OK) in the macro structure analysis measurement are defined as reference parameters for mass production. The best parameters for main frame welding are vertical position down (3G) with 170 Ampere current and 20 Volt voltages, and for horizontal position (2G) with 180 ampere current parameters and 17 Volt voltages.